Sleep disorder, an independent risk associated with arterial stiffness in menopause - Zhou, Yang; Yang, Ruwei; Li, Changbin; Tao, Minfang (Scientific reports, 2017)
As women age and go through menopause, they suffer a higher incidence of sleep disorder, cardiovascular morbidity and mortality. In addition, evidences suggested that sleep disorder was an important pathological indicator for coronary heart disease. However, the relationship between different menopausal status, sleep disorder and cardiovascular diseases was unclear. Thus, we aim to assess the association between sleep disorder with arterial stiffness in females of 40–60 years free of cardiovascular diseases through self-administered Pittsburgh Sleep Quality Index (PSQI) and brachial-ankle pulse wave velocity (baPWV). Logistic regression revealed that sleep disorder (PSQI score ≥ 8) was an independent indicator for higher risk of elevated arterial stiffness (baPWV ≥ 1465.5 cm/s, upper tertile) beyond other established cardiovascular confounders in peri-postmenopause (OR 2.83, 95% confidence interval (CI) 2.00–4.00, p < 0.001), but not in premenopause (OR 1.67, 95% CI 0.71–3.90, p = 0.223). Collectively, it clearly indicates that sleep disorder in menopausal women is of prominent value to predict arterial stiffness.